Isolationsmaßnahmen, Diagnostik und Organisation in deutschen Notaufnahmen während der COVID-19-Pandemie 2020 - Finke, M. (Med Klin Intensivmed Notfmed, 2021)
BACKGROUND: Since the beginning of the coronavirus disease 19 (COVID-19) pandemic, German emergency departments (ED) have been working in the area of conflict between high case load and demanding hygienic and organizational challenges. The aim of this study was to gain an overview of the current status of isolation measures, diagnostics and patient allocation of suspected COVID-19 cases. METHODS: Supported by the German Society for Interdisciplinary Emergency and Acute Medicine (DGINA) we invited leading ED physicians to answer an anonymous online survey regarding isolation measures, diagnostics and organization in emergency rooms during the COVID-19 pandemic. RESULTS: A total of 139 responders from all federal states and all levels of care took part in the survey. Standard operating procedures on COVID-19 exist in almost all participating EDs, although concrete measures to end isolation are often missing. Most EDs screen patients for the “classic” COVID-19 symptoms such as fever, respiratory symptoms or contact to positive subjects in a standardized fashion, although the threshold for prophylactic isolation varies greatly. The individual swab-testing and allocation strategies vary relatively strongly. Less than half of all EDs have a separate procedure for uninterrogatable patients (e.g. major trauma). In about 8% of suspected cases, COVID-19-specific thoracic computed tomography is performed in the ED. CONCLUSION: The current survey shows that the German EDs are well positioned for the moment, even though the isolation threshold is too high at some locations. In view of a possible increase in the number of cases during the winter season, a more precise differentiation of the previous recommendations of the Robert Koch Institute, especially for emergency admission patients, would be desirable. In this context, we propose a universal algorithm for the (de-)isolation of suspect cases in the ED.